A Case of Bilaterally Synchronized Faciobrachial Dystonic Seizures in Anti‐Leucine‐Rich Glioma Inactivated‐1 Encephalitis. Issue 4 (31st March 2020) - Mikami, Takahisa; Amano, Eiichiro; Iizuka, Takahiro; Machida, Akira
Abstract : View Supplementary Video 1